A comprehensive guide to sports physiology and injury management. An interdisciplinary approach (Elsevier, 2021)
Divided into two parts, physiology and sports injury management, this is an innovative clinical- and evidence-based guide, which engages with the latest developments in athletic performance both long and short term. It also considers lower level exercise combined with the pertinent physiological processes. It focuses on the rationale behind diagnostic work up, treatment bias and rehabilitation philosophy, challenging convention within the literature to what really makes sense when applied to sports settings. Drawing upon experts in the field from across the world and various sports settings, it implements critical appraisal throughout with an emphasis on providing practical solutions within sports medicine pedagogy.